PARADIGMA KRITIS TAFSIR PESANTREN: STUDI ATAS TAFSIR AL-IKLÎL FI MA`ÂNI AL-TANZÎL DAN TÂJ AL-MUSLIMÎN KARYA KH. MISHBAH MUSTHOFA - Ah. Haris Fahrudi (Universitas Kiai Abdullah Faqih Gresik, 2025)
This article discusses one of the interpretations of pesantren written by KH. Mishbah Mustofa. Kiai Mishbah's commentary shows his sharp analysis of a number of social realities in the community and weighs them with the messages of the Qur'an. This characteristic is one of the aspects that distinguishes it from the traditional interpretation paradigm in general which is textual, This study uses a descriptive analysis method of two KH interpretation works. Mustafa is Tafsir Al-Iklîl al-Iklîl fi Ma'ani al-Tanzîl and Tâj al-Muslimîn. The findings of this study are that the interpretation of the work of KH. Mustofa is based on a critical paradigm that aims to make the Qur'an a vital elan in forming an ideal social order. The paradigm of critical interpretation of KH. The Mishbah not only makes tafsir as a means to ground the Qur'an in the community through the local language, but also as a means of social control and a medium of liberation of the community from the structure and domination of the system that is unjust and contrary to the spirit of the Qur'an.